(untitled) (FEATURES AND PROBLEMS OF IMPLEMENTING ECONOMIC REFORMS IN AZERBAIJAN, 2025)
This study evaluates the country’s readiness for digital services, creating jobs on digital platforms, and encouraging innovation with minimal costs. The primary aim of the research is to analyze the factors influencing the economic potential of regions and identify key variables that can impact economic development. Regression analysis using the Eviews software package enabled the assessment of the relationship between variables and economic potential, revealing important factors for optimizing the potential of each region. The obtained results provide valuable insights for developing strategies and making economic decisions. Key words: Smart City, Smart Village, Economic Potential, Regional Development, Digital Transformation.